Revitalisasi Nilai Tradisi di Tengah Modernisasi: Dinamika Pesantren Jamiyatul Abror Cigalontang Tasikmalaya - Rahman, Adun; Fajri Faresi, Gilang Muhamad; Suhartini, Andewi; Harsing, Harsing; Alam, Ika Purnama; Hilman, Ahmad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to examine the dynamics of revitalizing traditional values at Pesantren Jamiyatul Abror Cigalontang Tasikmalaya in responding to the modernization of Islamic education. The background of this research arises from the phenomenon of transformation within pesantren education systems that face the challenges of globalization and digitalization, yet strive to preserve classical Islamic values such as adab (ethics), sincerity, and humility. This research employed a qualitative approach with a case study design, utilizing data collection techniques such as participatory observation, in-depth interviews, and document analysis. The findings reveal that the pesantren revitalizes its traditional values through three main strategies: integrating moral values into the formal curriculum, revitalizing the teaching of classical Islamic texts (kitab kuning) using digital tools, and strengthening the role of the kyai as a moral and spiritual exemplar. The modernization process does not diminish the pesantren’s identity but instead reinforces it through innovation grounded in Islamic values. The study concludes that Pesantren Jamiyatul Abror successfully developed an Adaptive Traditional Values Revitalization Model (RVT-A) a model of pesantren transformation that harmonizes tradition and modernity.